A Case Report of Adult Acne - Ivelina Yordanova; Desislava Tsvetanova; Diana Strateva; Pavlina Yordanova-Laleva; Dimitar Gospodinov (Journal of Biomedical & Clinical Research)
Acne vulgaris is among the commonest inflammatory skin diseases affecting pilosebaceous units. It occurs mainly in puberty and affects adolescents at the age of 14-19 years both females and males, in relation to sebum production of hair follicles under the action of sex hormones. Clinically the disease is presented with comedones, papules, pustules, nodules and scars in some cases. Seborrheic areas face, chest and back are affected. Recent epidemiologic studies have shown significant number of female patients aged over 25 years with acne and the term Adult onset acne (AOA)was established.The latter is manifested clinically in the lower third of the face. Primary etiological cause of AOAisahormonal imbalance, mainly hyperandrogenemia. Acase ofa25-year-old woman with adult acne and elevated levels of testosterone and prolactine is presented in this paper.